Exploring Students’ Perception on the Integration of Concept Mapping in Argumentative Writing - Hidayat, Taufik; Syahid, Abdul; Nurliana, Nurliana (Journal of English Language and Education, 2024)
Mind mapping is a creative, visual learning strategy that helps pupils grasp things more effectively. This study aimed to determine students' perceptions of using Mind Mapping using Xmind in writing classes. This study used a qualitative case study research method design. The data were collected through open-ended questionnaires and interviews. The subjects of this study were 6 active English students who had passed the argumentative course. Xmind became a tool for mind mapping approach to assist students in fulfilling their writing assignments. The findings indicated that students had a good attitude about utilizing mind mapping as an effective Visual teaching aid. Most students thought that mind mapping benefited them in writing essays, allowing them to be more creative and developing their ideas.